Impact of Various Nitrogenous Fertilizers on Wheat Crop Yield and Growth - Hussain, Amina; Azeem, Nobal; Riaz, Talha; Khan, Tahir Yab; Pehlwan, Babu; Amjad, Tayyaba; Muzammal, Muhammad; Sani, Imran Ali; Umm-E-Habiba; Sarfraz, Bushra (Indus Journal of Bioscience Research, 2025)
Nitrogenous fertilizers have increased crop yield, especially for essential crops such as wheat. This study assessed the effects of different nitrogen fertilizers (Urea, Ammonium Nitrate, Ammonium Sulfate, and Calcium Ammonium Nitrate) on wheat growth and yield. This research evaluated the impact of various nitrogen fertilizer types and application rates on essential wheat growth characteristics, such as plant height, tiller count, grain yield, and grain weight. A randomized complete block design (RCBD) was employed for field trials in the growing season, featuring three replicates for each treatment. Fertilizer treatments comprised different application rates of Urea (120, 180, 240 kg/ha), Ammonium Nitrate, Ammonium Sulfate, and Calcium Ammonium Nitrate. The research gathered wheat growth metrics and yield data, which ANOVA examined to identify significant differences among treatments. The findings indicated that Urea (240 kg/ha) resulted in the most significant plant height, tiller count, grain production, and grain weight, significantly surpassing other fertilizer applications. Ammonium Nitrate exhibited comparable beneficial benefits, whereas Ammonium Sulfate and Calcium Ammonium Nitrate showed relatively subdued impacts on wheat productivity. The findings indicated that improving the application of nitrogen fertilizer, specifically Urea, might substantially enhance wheat crop yield and growth, thus promoting more effective agricultural methods. The study emphasized the significance of nitrogen management in wheat cultivation and provided critical insights for enhancing fertilizer utilization efficiency and sustainability. Additional research is required to investigate the long-term impacts of these fertilizers on soil health and environmental impact. Nitrogen fertilizers, especially Urea at 240 kg/ha, significantly enhance wheat growth, yield, and sustainability, necessitating further research on environmental impacts.